Foucault for architects - Fontana-Giusti, Gordana (Abingdon, Oxon : Routledge, 2013)
"Offering an excellent entry point into the remarkable work of Michel Foucault, this book provides a focused overture suitable for architects, designers, urban designers, students of architectural design and related histories and theories. Michel Foucault
Includes bibliographical references and index. 1. Positioning -- 2. Archaeology -- 3. Enclosure -- 4. Bodies -- 5. Spatiality/aesthetics. Also available in print edition. Mode of access: World Wide Web.
Keywords: Foucault, Michel, 1926-1984.; Foucault, Michel, 1926-1984.; Architecture -- Philosophy; Mimarlık -- Felsefe